Douglas C. Harr letter to Peter C. Petersen regarding bird sightings, June 23, 1977 - Harr, Douglas C.et al (1977)
Letter from Douglas C. Harr to Peter C. Petersen regarding bird sightings, June 23, 1977. The document includes sightings of Black-Crowned Night Herons and Forester Terns at West Hottes Lake in Dickinson County, Canvasback Hens at Mud Lake in Clay County, and a Double Crested Cormorant at Lilly Lake in Dickinson County. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of summer 1977. Epson - sheet feed/flatbed